Herpes zoster related healthcare burden and costs in immunocompromised (IC) and IC-free populations in England: an observational retrospective database analysis. Issue 8 (27th August 2019) - Curran, Desmond; Hunjan, Manjit; El Ghachi, Amale; El-Hahi, Yassine; Bianco, Veronique; Ferreira, Germano
Abstract : Objective: Individuals with immunocompromised (IC) conditions are at a higher risk of developing herpes zoster (HZ) than IC-free individuals. This study assessed the healthcare resource utilisation (HCRU) burden and costs, of HZ in IC and IC-free individuals ≥18 years of age (YOA). Methods: We conducted an observational retrospective study in a cohort of IC (n=621 588) and IC-free (n=621 588) individuals, matched by age, gender and General Practitioner practice region, contributing to the Clinical Practice Research Datalink database from 2000 to 2012 and linked to the Hospital Episode Statistics inpatient data. HCRU (ie, primary and secondary care consultations, hospital inpatient stays and treatment prescriptions) was analysed from 7 days before to: (1) 30, (2) 365 days after the HZ diagnosis date for individuals with (1) HZ only (no postherpetic neuralgia (PHN)) and (2) individuals with HZ and PHN only. Healthcare costs were computed by multiplying the number of units of resources used by the unit costs, summed across all HCRU categories to obtain a total cost per subject. Values were expressed in 2014 UK pound sterling (£) and presented for HZ cases overall, stratified by age (ie, 18–49, 50–59, 60–69, 70–79 and ≥80 YOA) and IC status. Results: The percentage of HZ cases requiring hospitalisation was higher in IC individuals (2.7% vs 0.4% in IC and IC-free individuals aged 18–49 YOA, respectively and 9.5% vs 7.5% in IC and IC-free individuals aged ≥80 YOA, respectively). Similarly, HZ-related mean treatment costs per subject were higher in IC individuals (£189 vs £104 in IC and IC-free individuals aged 18–49 YOA, respectively and £557 vs £401 in IC and IC-free individuals aged ≥80 YOA, respectively). Costs varied considerably by IC condition. Conclusions: Individuals with IC conditions, have a high burden of HZ, associated with an increased risk of HZ and high HZ-related healthcare costs.